Dredging - Yell, Denis (ICE design and practice guide., 1995)
This guide highlights the particular problems of excavating from underwater sites, and describes the methods and equipment developed to overcome them. All the stages of dredging are considered, from project design specification and site investigation, to supervision of the actual dredging works.